STUDI TRANSPOR KREATININ MENGGUNAKAN MEMBRAN KOMPLEKS POLIELEKTROLIT (PEC) KITOSAN-PEKTIN - , NI PUTU SRI AYUNI; , Dr. Dwi Siswanta, M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A study of creatinine transport using chitosan-pectin polyelectrolyte complex (PEC) membranes had been conducted. Membranes were synthesized with variations of the chitosan-pectin PEC membranes composition of (70:30), (80:20), (90:10) and later used for creatinine transport with concentrations of 70, 100, dan 130 ppm. Membranes with the optimum creatinine diffusion result were used to synthesize Molecularly Imprinted Polymer (MIP). The MIP and non-MIP chitosan-pectin membranes were also used for the competition of creatinine, urea and vitamin B12 transport. Chitosan-pectin PEC membranes were synthesised and characterised using the infrared (IR) spectrophotometer, measurement of tensile strength and strain, scanning electron microscopy (SEM) analysis. Then, Creatinine and solution of the three competitions (creatinine, urea and vitamin B12) that has been passed through the membranes were analysed for the diffused creatinine and flux values in the MIP or non-MIP chitosan-pectin membranes. The results of chitosan-pectin PEC membrane characterization using IR spectrophotometer indicated the presence of ionic interactions between the carboxyl groups of pectin and amino groups of chitosan at wave number 1604 cm-1. The best result of non-MIP membrane transport composition ratio was 70:30. The initial concentrations of creatinine were 70, 100, and 130 ppm, resulting diffusions of creatinine of 24.29, 24.63, and 25.24% with flux values of 3.87Ã10-4, 6.34Ã10-4 and 6.53Ã10-4 g/m2s, respectively. The results of diffusion of creatinine using MIP membrane were 26.80, 27.53 and 28.59% with flux values of 5.88 Ã10-4, 6.56Ã10-4 and 7.00Ã10-4 g/m2s. Result of the competition transport between creatinine, urea and vitamin B12 using non-MIP chitosan-pectin PEC membrane produced higher diffused urea. Meanwhile, higher diffused creatinine was produced in membranes with MIP.